FUNGSI PERATURAN PERUNDANG-UNDANGAN DALAM PENYELENGGARAAN BIROKRASI PEMERINTAHAN - Freddy Poernomo (UIN Sunan Gunung Djati Bandung, 2022)
Governance is impossible without legislation and bureaucracy. Legislation is a source of government authority, both binding authority and discretionary authority, while the bureaucracy moves the wheels of government. The implementation of the wheels of government by the bureaucracy must be based on the authority according to the laws and regulations and the irregularities have legal implications in the form of legal responsibility by the bureaucracy. Deviations in the implementation of government authority by the bureaucracy can be in the form of abuse of authority, arbitrary actions, or arbitrary actions. The act of abuse of authority by the bureaucracy occurs when the three bureaucracies use their authority differently from the purpose for which the authority is granted by legislation. Arbitrary action when the bureaucracy does not give adequate consideration in making decisions or taking other actions. Actions without authority are bureaucratic actions that violate the limits of authority in the form of substance, time, or place. Bureaucratic responsibility due to irregularities in the implementation of authority can be in the form of administrative responsibilities such as canceling decisions that have been issued or criminal liability if the deviation has implications for state financial losses.